2004
DOI: 10.1002/ptr.1617
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of some common ingredients of traditional chinese medicine, Angelica sinensis, Lycium barbarum and Poria cocos

Abstract: The antioxidant activities of three popular ingredients of traditional Chinese medicine, namely Angelica sinensis (AS), Lycium barbarum (LB) and Poria cocos (PC) were evaluated in this study. The results showed that aqueous extracts of these crude drugs exhibited antioxidant activities in a concentration-dependent manner. All extracts displayed an inhibitory effect on FeCl2-ascorbic acid induced lipid peroxidation in rat liver homogenate in vitro, with the order of activity LB > AS > PC. The tested extracts sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 22 publications
2
74
0
4
Order By: Relevance
“…In support of a role for the anti-oxidant properties of Lycium barbarum (Amagase et al, 2009b;Wu et al, 2004;Gong et al, 2005) in the attenuation of the effects of exercise on cortisol release are the results of Davison, et al (2007). Similar to the current results, they showed that dietary supplementation with anti-oxidants (daily vitamin C (L-ascorbic acid, 1000 mg) and vitamin E (RRR-alpha-tocopherol, 400 IU) supplementation) blunted the cortisol response to a single prolonged exercise challenge (Davison et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…In support of a role for the anti-oxidant properties of Lycium barbarum (Amagase et al, 2009b;Wu et al, 2004;Gong et al, 2005) in the attenuation of the effects of exercise on cortisol release are the results of Davison, et al (2007). Similar to the current results, they showed that dietary supplementation with anti-oxidants (daily vitamin C (L-ascorbic acid, 1000 mg) and vitamin E (RRR-alpha-tocopherol, 400 IU) supplementation) blunted the cortisol response to a single prolonged exercise challenge (Davison et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…14) Our previous study also proved that pretreatment with LBP (200 mg/kg), the main antioxidant in Lycium barbarum, significantly attenuated DOX-induced cardiac myofibrillar disarrangement in rats. LBP was also effective in decreasing the levels of serum CK to improve conduction abnormalities caused by DOX exposure.…”
Section: Discussionmentioning
confidence: 78%
“…22) Compound 2 was obtained as sticky oil with small amount. Its molecular formula was determined as C 23 13 C-NMR and DEPT spectra showed two aromatic rings with carbon signals for 9 methines, 2 methylenes, 5 methyls, and 7 quaternary carbons, which supported that the extra degree of unsaturation except two phenyl rings was presumed to be due to tetrahydrofuran ring. The 8.8Ј-linked tetrahydrofuran skeleton between two propanyl groups was certified by good connectivities in the 1 H-1 H COSY spectrum, which showed correlations between H-8 with H-7/H-9/H-8Ј and H-8Ј with H-7Ј/H-9Ј/H-8.…”
mentioning
confidence: 85%